Can a novel computerized cognitive screening test provide additional information for early detection of Alzheimer's disease?. Issue 6 (20th March 2014) - Tarnanas, Ioannis; Tsolaki, Magda; Nef, Tobias; M. Müri, René; Mosimann, Urs P.
Abstract: Background: Virtual reality testing of everyday activities is a novel type of computerized assessment that measures cognitive, executive, and motor performance as a screening tool for early dementia. This study used a virtual reality day‐out task (VR‐DOT) environment to evaluate its predictive value in patients with mild cognitive impairment (MCI). Methods: One hundred thirty‐four patients with MCI were selected and compared with 75 healthy control subjects. Participants received an initial assessment that included VR‐DOT, a neuropsychological evaluation, magnetic resonance imaging (MRI) scan, and event‐related potentials (ERPs). After 12 months, participants were assessed again with MRI, ERP, VR‐DOT, and neuropsychological tests. Results: At the end of the study, we differentiated two subgroups of patients with MCI according to their clinical evolution from baseline to follow‐up: 56 MCI progressors and 78 MCI nonprogressors. VR‐DOT performance profiles correlated strongly with existing predictive biomarkers, especially the ERP and MRI biomarkers of cortical thickness. Conclusions: Compared with ERP, MRI, or neuropsychological tests alone, the VR‐DOT could provide additional predictive information in a low‐cost, computerized, and noninvasive way.